Fully Online In-demand Skill Training: Understanding Participant’ Reason and Reaction - Batita, Maurish Sofie Rahmi; Agus Wedi; Sulthoni (Journal of Technical Education and Training, 2023)
Gaining skills will aid the youth generation to obtain career opportunities and while also making their workforce efficient and in line with the current industry in the era of the 21st century. However, skill demands by industry are typically gained outside formal education settings. Thus, a new paradigm of learner-directed study has emerged as a promising development for educational sectors. This study proposes a skill-based training based on the in-demand hard-skill industry in online settings, and an investigation of participant reason and reactions to the training. The study attempted online training in the topics of User Interface and User Experience (UIX) and Social Media Marketing, which were discovered to be in demand within the Indonesian workforce. The study was able to employ 434 Indonesian registrants, however, only 151 were able to complete the post-training questionnaire. The study’s analysis revealed that the majority of participants were university students looking to improve their skill sets before entering the job market. The learners responded positively to the training procedures and learning approaches. This study concluded that skill-based online training has the potential to improve industry-required skills.